Experimental Study of the Flame Retardancy of PMMA-Graphene Composite Materials - Al-Jarrah, Jawdat Abdallah; Rbeht, Diana; Al-Waqfi, Mohammed S. El-Ali; Al-Jahmany, Yarub (Engineering, Technology & Applied Science Research, 2024)
In this paper, Polymethyl methacrylate (PMMA)-graphene nano-composites were prepared and tested with the use of a cone calorimeter. Graphene was added to PMMA in limited weight percentages to improve the flame retardancy of PMMA. Two samples of PMMA-graphene, namely 1 and 3 wt%, were investigated. The combustion properties of the tested samples of PMMA-graphene composites, mass loss rate, heat release rate, and time to ignition were measured and calculated. It was found that the peak heat release rate of PMMA-graphene composites reduced by 17% when 3 wt% graphene was added to pure PMMA. Adding graphene to PMMA improves the thermal stability of PMMA by reducing the time of ignition. Also, the presence of graphene enhanced the formation of a continuous carbonized layer at the surface of the burned PMMA.